Aspects Of Saf Smelting Of Ferrochrome (The Southern African Institute of Mining and Metallurgy, 2004)
This paper provides a review of the chemical reactions occurring in the submerged arc processing of chromite ores. The excavations of industrial furnaces have shown that the charge, as it descends through the furnace, passes through a number of distinct reaction zones. Each zone is characterised by differing process conditions and reaction products. The phase equilibria, reaction steps and mechanisms occurring as the charge progresses through the furnace are examined, and the potential influences of these factors on the process outcomes are discussed.